Anti-vascular endothelial growth factor therapy for diabetic macular edema. (December 2013) - Boyer, David S.; Hopkins, J. Jill; Sorof, Jonathan; Ehrlich, Jason S.
Diabetes mellitus is a serious health problem that affects over 350 million individuals worldwide. Diabetic retinopathy (DR), which is the most common microvascular complication of diabetes, is the leading cause of new cases of blindness in working-aged adults. Diabetic macular edema (DME) is an advanced, vision-limiting complication of DR that affects nearly 30% of patients who have had diabetes for at least 20 years and is responsible for much of the vision loss due to DR. The historic standard of care for DME has been macular laser photocoagulation, which has been shown to stabilize vision and reduce the rate of further vision loss by 50%; however, macular laser leads to significant vision recovery in only 15% of treated patients. Mechanisms contributing to the microvascular damage in DR and DME include the direct toxic effects of hyperglycemia, sustained alterations in cell signaling pathways, and chronic microvascular inflammation with leukocyte-mediated injury. Chronic retinal microvascular damage results in elevation of intraocular levels of vascular endothelial growth factor A (VEGF), a potent, diffusible, endothelial-specific mitogen that mediates many important physiologic processes, including but not limited to the development and permeability of the vasculature. The identification of VEGF as an important pathophysiologic mediator of DME suggested that anti-VEGF therapy delivered to the eye might lead to improved visual outcomes in this disease. To date, four different inhibitors of VEGF, each administered by intraocular injection, have been tested in prospective, randomized phase II or phase III clinical trials in patients with DME. The results from these trials demonstrate that treatment with anti-VEGF agents results in substantially improved visual and anatomic outcomes compared with laser photocoagulation, and avoid the ocular side effects associated with laser treatment. Thus, anti-VEGF therapy has become the preferred treatment option for the management of DME in many patients.